Effectiveness of a Problem-Based Learning Module in Improving Sports Injury Management Skills among Prospective Elementary School Teachers - Anton Sukowati; Supriyati Fatma Rabia; Meilin A N Azizah; M Fadli (Journal Evaluation in Education (JEE), 2026)
Purpose of the study: This study aims to evaluate the validity, practicality, and effectiveness of a Problem-Based Learning (PBL) module designed to strengthen sports injury management competence among prospective elementary school teachers. Methodology: The research employed a Research and Development design using the ADDIE model, with data collected through expert validation sheets, lecturer and student practicality questionnaires, and pretest–posttest learning outcome tests. Data analysis was conducted using descriptive statistics, paired sample t-tests, and N-Gain analysis with SPSS software. Main Findings: The results showed that the module achieved high expert validity (92%) and strong curriculum alignment (96%). Practicality evaluation indicated very good acceptance from students (88.2%) and lecturers (91.6%). Learning outcomes improved significantly from a pretest mean score of 63.5 to a posttest mean score of 84.2 (p < 0.05), supported by a moderate N-Gain value of 0.567. Novelty/Originality of this study: The novelty of this study lies in the development of a PBL-based module specifically focused on sports injury management and first aid training for prospective teachers, supported by a multi-party evaluation approach involving experts, lecturers, and students, which provides a comprehensive assessment of the module’s feasibility and contributes to strengthening safety literacy in physical education contexts.